Computer architecture and organization : an integrated approach / Miles J. Murdocca, Vincent P. Heuring - Murdocca, Miles (Wiley series in electrical and computer engineering, 2007)
An accessible introduction to computer systems and architecture Anyone aspiring to more advanced studies in computer-related fields must gain an understanding of the two parallel aspects of the modern digital computer: programming methodology and the underlying machine architecture.